Problem identyfikacji centrów odpowiedzialności w szpitalu - Czechowska, Anna (Identification of Responsibility Centres in the Hospital, 2005)
Hospitals currently functioning in Poland are huge and complex organizations which not long ago found themselves in the free market reality. Current condition of the Public Health Care system requires, however, that individual units developed the existing systems of control and performance measurement. Each hospital in order to ensure the possibility of a stable growth needs to elaborate a suitable and adapted to individual conditions system of controlling, measuring and planning of costs and incomes related to them. A helpful solution is the conception of responsibility accounting centres. The article attempts to describe the sophisticated reality of a hospital from the perspective of managing through responsibility centres. The author describes sample usage of cost and income centres in a hospital. She also indicates the difficulties which arise when applying the solutions typical of commercial enterprises to hospitals, which are non-for-profit organizations functioning on a not fully competitive market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (2); 2005; nr 1059, s. 407-417